Relationship of blood heavy metals and osteoporosis among the middle-aged and elderly adults: A secondary analysis from NHANES 2013 to 2014 and 2017 to 2018 - Huang, Zengfa; Wang, Xiang; Wang, Hui; Zhang, Shutong; Du, Xinyu; Wei, Hui (Frontiers in Public Health, 2023)
Objective: This study aims to assess the relationship of blood heavy metals with the higher prevanlence of osteoporosis in the middle-age and elderly U.S. adults using the National Health and Nutritional Examination Surveys (NHANES). Methods: The secondary data analysis was performed using the data NHANES 2013-2014 and 2017-2018. We used the information provided by participants in NHANES including physical examination, laboratory tests, questionnaire and interview. Logistic regression and weighted quantile sum regression (WQS) models were used to explore the relationships between blood heavy metals and osteoporosis. Results: A total of 1777 middle-age and elderly participants were analyzed in this study, comprising 115 with osteoporosis and 1662 without. Adjusted model 1 showed a significant positive relationship between cadmium (Cd) levels and osteoporosis (quartile two, OR = 7.62; 95% CI, 2.01-29.03; p = 0.003; quartile three, OR = 12.38; 95% CI, 3.88-39.60; p <0.001; quartile four, OR = 15.64; 95% CI, 3.22-76.08; p = 0.001). The fourth quartile of selenium (Se) level (OR = 0.34; 95% CI, 0.14-0.39; p <0.001) led to a lower prevalence of osteoporosis and exerted a protective effect in model 1. Other Models produced similar results to model 1. Subgroup analysis showed Cd levels was positively related with the higher prevalence of osteoporosis in three models in females, while this relationship was not found in males. The fourth quartile of Se level was related with lower prevalence of osteoporosis in both males and females analysis. Significant positive relationship was found between blood Cd level and the prevalence of osteoporosis in the non-smoking subgroup. Blood Se level showed a protective effect in fourth quartile in both the smoking and non-smoking subgroups Conclusion: Blood Cd level aggravated the prevalence of osteoporosis while blood Se level could be a protective factor in osteoporosis among the U.S. middle-age and older population.